Economic Recovery Strategy after the COVID-19 Pandemic - Yuliana . (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2021)
The COVID-19 pandemic has been more than one year. It was started in March 2020. All aspects of life have been changed. Almost every activity must be done at home. This causes some businesses to close. Economic flow is not good since then. The economic recovery strategy must be done to restore the economic growth after the COVID-19 pandemic subsided. This paper aims to describe the strategy in economic recovery after the COVID-19 pandemic. Methods: This paper is a literature review. The literature was taken from Science Direct and PubMed databases. Keywords are COVID-19, economy, recovery, strategy. The results showed that the economic recovery strategy must be done gradually in all aspects. The aspects that must be developed are broadband, healthcare investment and facilities, aviation, stock markets, and transportation. Broadband is very essential in online working, business, and learning. Healthcare investment is very critical to shorten the lockdown period. Those strategies can alleviate the economic crisis and increase economic growth.  Keywords: COVID-19, economy, recovery, strategy JEL : A10, O1, Z18